Macrocyclization of 3-triflyloxybenzynes with tetrahydrofuran via an anionic thia-Fries rearrangement. Issue 48 (15th May 2020) - Cheng, Ruixiang; Xiong, Wenfang; Qi, Chaorong; Wang, Lu; Ren, Yanwei; Jiang, Huanfeng
Abstract : An uncommon macrocyclization reaction between 3-triflyloxybenzynes and tetrahydrofuran leading to novel 19-membered polyether macrocycles is reported. Abstract : A novel and uncommon macrocyclization reaction between 3-triflyloxybenzynes and tetrahydrofuran has been developed for the first time, providing a direct method for the synthesis of a range of functionalized 19-membered polyether macrocycles in moderate to good yields. The process was proposed to proceed through an anionic thia-Fris rearrangement under transition metal-free conditions, leading to the formation of four new C–O bonds and one new C–S bond in a single step.